Methodological and ethical aspects of conducting focus tests with representatives of the institutional support system for families with alcohol problems - Dobińska, Gabriela; Walczak‑Człapińska, Karolina (Rodzina w systemie wsparcia i pomocy osobom z problemem alkoholowym, 2020)
The aim of the article is to reflect on the ethical and methodological dilemmas experienced by researchers during planning and implementation of focus studies with representatives of the institutional support system for families with alcohol problems. The first part includes the main theoretical assumptions concerning the implementation of focus studies, pointing to the variety of approaches, doubts and dilemmas resulting, among others, from the status of the methodological examination of the focus group, elements of the research procedure, ethics, selection of participants, the analysis of the collected empirical material, the role of the moderator, the selection of space and the method of registration of the study. In the subsequent methodological part, the researchers presented the detailed course of the research procedure, which provides an introduction for the third and final analytical part, in which the authors present dilemmas, as well as ways of dealing with methodological constraints, simultaneously indicating the potential and opportunities related to focus tests. The focus interview carried out by the researchers with representatives of support institutions for families with alcohol problems was part of a wider research project. The article is a result of a project titled “Family in the system of social support and help for people with alcohol problems. Biographical research with the participation of parents of adult children addicted to alcohol” carried out as the following task: “Supporting scientific research in the area of problems resulting from the use of alcohol”. The project conducted by the research team from the Special Pedagogy Laboratory at the Faculty of Education Sciences is financed by the Gambling Problem Solving Fund, as part of the National Health Program for the years 2016–2020.